Requirement of micronutrients and oligoelements - Ciudad Reynaud, Antonio (2014)
A brief evidence-based account on the importance of micronutrients and oligoelements in the diet during pregnancy and post-partum is done. An integral approach on nutrition must be given to women during reproductive life as well as before pregnancy. Micronutrient deficiencies have been associated with fetal structural defects risks. Micronutrient supplementation during pregnancy has shown to be effective in the prevention of different health problems including low birth weight, small for gestational age, and birth defects including neural, cardiovascular, cleft palate and abnormalities of the urinary tract. There is no evidence of protection against genetic problems type Down syndrome, or in reduction of perinatal mortality.